The association between social support and postpartum post-traumatic stress disorder - Jingfen Chen; Shu Wang; Xiaolu Lai; Linli Zou; Shi Wu Wen; Daniel Krewski; Ri-hua Xie (BMC Pregnancy and Childbirth, 2024)
Abstract Background Postpartum post-traumatic stress disorder (PTSD) is a debilitating condition that can arise following childbirth. Despite a growing body of research on postpartum mental health, the relationship between social support and postpartum PTSD remains unclear. This study aimed to assess the association between social support and postpartum PTSD. Methods A prospective cohort study was conducted at a tertiary hospital in Guangdong province of China between November 2022 and April 2023. Eligible mothers were assessed for social support using the Social Support Rating Scale (SSRS) at three days postpartum and for PTSD using the Perinatal Post-Traumatic Stress Disorder Questionnaire (PPQ) at 42 days postpartum. The association between social support and postpartum PTSD was analyzed using multiple linear and log-binomial regression, with adjustments for potential confounders. Results Forty-six of 560 (8.2%) mothers developed PTSD within 42 days postpartum. Scores for subjective support (β=-0.319, P < 0.001), objective support (β=-0.327, P < 0.001), support availability (β=-0.285, P < 0.001), and overall social support score (β=-0.428, P < 0.001) were inversely associated with PTSD scores. Compared to mothers in the 1st quartile of the overall social support score, those in the 2nd, 3rd, and 4th quartiles had adjusted relative risks of 0.39 (95% confidence interval [CI]: 0.21–0.74), 0.20 (95% CI: 0.09–0.45), and 0.10 (95% CI: 0.03–0.33), respectively, of developing PTSD. An inverse linear trend in the risk of PTSD was observed with increasing social support (P-trend < 0.001). Conclusions Social support may have a protective effect against postpartum PTSD, with practical implications for interventions targeting various dimensions of support.